Computer-aided design to support fabrication of wrist splints using 3D printing: A feasibility study. (December 2014) - Paterson, Abby M; Donnison, Ella; Bibb, Richard J; Ian Campbell, R
Introduction: Issues contributing to poor patient compliance for splint wear include poor aesthetics, fit and performance. This paper describes a novel digitised splinting process using 3D printing in an attempt to overcome these issues. The output of the investigation was the creation of a specialised computer-aided design software workflow to support 3D printing, developed specifically for splinting practitioners in the UK, to enable them to design splints themselves for each individual patient. Method: A small-scale feasibility study was done, based on the current splinting process. A thorough literature review and physical engagement in current splinting practice was performed, highlighting key requirements for successful splint fabrication. Key requirements were then replicated in a virtual software environment. Opportunities for integrating new, novel features were explored. The key requirements were then refined into a specialised software workflow to replicate the splinting process. The specialised software was then evaluated by 10 practitioners. User trials of the software were performed, followed by semi-structured interviews. Audio recordings were transcribed and then coded to establish similar trends of opinions, and areas for future research. No patients or vulnerable participants were involved in the study. Results: All participants were able to use and navigate around the software prototype with relative ease. Strengths included potential simplicity in modelling more complex splints, but several areas for future research are identified, including cost analysis and materials development. Discussion: The digitised splinting process shows promise for the benefit of both practitioners and their patients, provided that future research and investment can overcome current limitations.